Wykonaj redukcję wyrazów podobnych
1.0,3c³-0,2c³-0,6c³+c²
2. 5d²-1,5d³-½d²-0,8+d³-2,2

Wykonaj odejmowanie
a) (0,4ab-0,5bc+0,1cd)-(-0,3ab+2,5bc-cd)
b) (4xn +2xm+5) - ( xn+xm+6)

Wykonaj dodawanie
c) (5x²-ax+a²)+(3x²+2ax-3a²)
d) (10an-2bm+c)+(-3an-6bm-c)

1

Odpowiedzi

2009-11-30T15:10:15+01:00
Wykonaj redukcję wyrazów podobnych
1.0,3c³-0,2c³-0,6c³+c² = -0,5c³+c²
2. 5d²-1,5d³-½d²-0,8+d³-2,2= 4½d²-½d³-3

Wykonaj odejmowanie
a) (0,4ab-0,5bc+0,1cd)-(-0,3ab+2,5bc-cd)=0,4ab-0,5bc+0,1cd+0,3ab-2,5bc+cd= 0,7ab-3bc+1,1cd
b) (4xn +2xm+5) - ( xn+xm+6) = 4xn +2xm+5 - xn -xm-6= xm + 3xn- 1

Wykonaj dodawanie
c) (5x²-ax+a²)+(3x²+2ax-3a²) = 5x²-ax+a² + 3x²+2ax-3a² = ax-2a² + 8x²
d) (10an-2bm+c)+(-3an-6bm-c)= 10an-2bm+c-3an-6bm-c= 7an -8bm
1 3 1